Analisis Faktor-Faktor yang Mempengaruhi Motivasi Kerja Karyawan Pada PT. Bank Syariah Mandiri Cabang Harapan Raya Pekanbaru - Saragih, Hendra; Fri Sella Afriani (Bedelau: Journal of Education and Learning, 2021)
The purpose of this study was to determine the influence of service quality delivery of goods on The purpose of this study was to determine the factors that affect employee motivation at PT. Bank Syariah Mandiri Branch of Harapan Raya Pekanbaru. The sample in this study were employees at PT. Bank Syariah Mandiri Branch Harapan Raya Pekanbaru, amounting to 34 people. While the variables examined in this study are internal factors, external factors and work motivation. Data analysis used multiple linear regression method using validity, reliability, normality test, heteroscedasticity test, multicollinearity test, durbine Watson test, F test, R2 test and t test. The test is conducted to determine the relationship between the independent variable and the dependent variable. Based on the results of the research that internal factors and external factors simultaneously affect employee work motivation with a correlation value of R = 0.698 which indicates a close relationship between internal factors and external factors with employee work motivation at PT. Bank Syariah Mandiri Branch of Harapan Raya Pekanbaru. Meanwhile, R square was obtained 0.454, which means that internal factors and external factors contributed 45.4% to the work motivation of employees at PT. Bank Syariah Mandiri Harapan Raya Pekanbaru Branch. Partially, it is obtained that the internal factor variable has a positive and significant effect on employee motivation at PT. Bank Syariah Mandiri Harapan Raya Pekanbaru Branch with a significant 0.001 less than alpha 0.05. The results of the F test show that F counts 14.697> F table 3.30, which means that simultaneously it shows that internal factors and external factors on employee work motivation at PT. Bank Syariah Mandiri Branch of Harapan Raya Pekanbaru. The multiple linear regression equation is as follows: Y = 4.409 + 0.987X1 + 0.460X2.